Urinary leukotriene e4 level profile in various degrees of severity in atopic dermatitis patients in dermatovenereology outpatient clinic Dr. Soetomo General Hospital, Surabaya: A descriptive study - Pratamasari, Meita Ardini; Hoetomo, M. Marsoedi; Hidayati, Afif Nurul (Dermatology Reports, 2019)
Atopic dermatitis (AD) is a chronic, relapsing skin inflammatory disease. Corticosteroid as the cornerstone treatment for AD has some flaw, especially for the chronic recalcitrant AD, since it has side effects and high possibility of rebound. Leukotriene receptor antagonist (LTRA) which has been used for asthma and allergic rhinitis now has been developed for treating AD, based on the similar mechanism of inflammation. Leukotriene (LT) is an inflammatory mediator that is thought to play role in the asthma, allergic rhinitis, and AD. Urinary leukotriene E4 (U-LTE4), the stable metabolite of LT, can be found in urine. This research aims to evaluate the role of LT in various degrees of severity in AD patients by measuring U-LTE4 levels using Enzyme Linked Immunosorbent Assay (ELISA). Twenty two AD patients who were in a flare state and came to the outpatient clinic on April – July 2017 were measured their U-LTE4 levels. The results demonstrated that mean of U-LTE4 levels increases consistently with intensity of the degree of severity, and this finding supports previous study that LT plays role in AD.